Advancing Entrepreneurship and SME Growth through Business Incubation - He, Junda; Ma, Henry; Wang, Mengxia (International Journal of Social Sciences and Public Administration, 2025)
The prevalence and efficacy of entrepreneurship are influenced by a variety of factors that have a local component: either they are greatly influenced by local events, or they are better served by initiatives developed and carried out locally. Local business incubators can encourage entrepreneurship. By offering a range of services and tools for business support created and maintained by incubator management and accessible through a network of connections and inside the incubator, business incubators aim to hasten the successful expansion of entrepreneurial ventures. The major goal of this essay is to explain how incubators help small and medium-sized businesses. Businesses contribute to Slovakia's knowledge-based economy" According to the VEGA project 1/0654/11, "Innovative miniature and moderate enterprises as a section of the knowledge-based economy in Slovakia," this study was conducted. It is divided into three sections: the first discusses the basics of incubators, including their types and goals; the second emphasizes how business incubators help to promote the local aspect of entrepreneurship; and the third explains how business incubators were established in Slovakia and how they serve as a instrument to assist Slovakian SMEs focused on technology and to facilitate the start-up of new businesses.